A Delphi study on the supply risk-mitigating effect of additive manufacturing during SARS-COV-2. Issue 4 (October 2022) - Meyer, Matthias M.; Glas, Andreas H.; Eßig, Michael
Abstract: Procurement has faced major challenges due to the collapse of global supply chains in the course of the SARS-COV2 pandemic, and non-critical items have become critical bottlenecks. Additive manufacturing (AM) is an emerging technology that serves as a local supply source and can mitigate some of these bottlenecks. For example, it was possible to source medical spare parts and protective equipment via AM, even when the globally arranged traditional (formative or subtractive manufacturing) supply sources failed. To that end, this research examines how supply risks change when sourced via an AM supply source rather than through supply sources that use traditional manufacturing (TM). This study assesses supply risk using a Delphi study from July to October 2020. The findings were further explored using discriminant analysis. A mix of TM supply sources with AM ('hedging') can minimise the overall supply risks. The discussion conceptualises a portfolio model to determine whether to source demands via TM, AM, or by hedging. The implications of hedged manufacturing are linked to the modern portfolio theory. Highlights: Additive Manufacturing supply risk. Risk assessment. Delphi Study. Discriminant Analysis.